Исследование свойств порошков алюминия, полученных в аргоне с добавками кислорода; Известия вузов. Физика; Т. 55, № 6/2 (приложение) - Яворовский Н. А. Николай Александрович; Пустовалов А. В. Алексей Витальевич; Лобанова Г. Л. Галина Леонидовна; Журавков С. П. Сергей Петрович (2012, 2012)
Заглавие с экрана